The Capacity Limits of Roundabouts - Andrea Kocianova (Communications - Scientific letters of the University of Zilina, 2014)
According to the manuals for the capacity calculation and evaluation of roundabouts it is possible to calculate and evaluate the capacity of roundabout entries only under particular traffic conditions. However, it is not possible to simply determine the total capacity of roundabouts. For this reason, custom software tool, which allows total capacity calculation for different models of roundabouts under different traffic conditions, has been created. Results of the maximum capacity limits for some of the analyzed roundabouts at the most influencing traffic conditions settings are shown in the article. For better illustration, the results are compared with maximum capacity limits of simple unsignalized intersection.